Correlação entre os casos confirmados de dengue e fatores climáticos em regiões de saúde do estado do Tocantins - D'Ambros , Izabela Medina (Universidade Federal do Tocantins, 2023)
The three most expressive arbovíruses in Brazil are dengue (DENV), Zika (ZIKV) and Chikungunya Fever (CHIKV). Aedes aegypti (A. aegypti) and Aedes albopictus are the main vectors that transmit the vírus of these diseases. Its occurrence becomes more favored in regions with hot and humid climates, such as Brazil. The State of Tocantins is considered endemic for the risk of epidemic for arbovíruses. The macro-research aimed to correlate meteorological factors (rainfall, humidity and temperature) and the co-circulation of arbovíruses in the health regions of Tocantins. This study focuses only on dengue data and results and on precipitation and humidity factors. The research is justified by the lack of systematized data from proven cases of dengue and stratified by health regions. The production of data and information directly implies a more effective confrontation of the problem, enabling the evaluation and development of public policies oriented to the fight against dengue in a regionalized way. The numbers of confirmed cases of dengue were obtained through the Health Surveillance Superintendence of the Tocantins State Department of Health (SVS/SES-TO and the climatic ones through the National Institute of Meteorology (INMET). cross-sectional, retrospective, quantitative, descriptive and analytical, with data collected from 2016 to 2019, statistically treated by the Shapiro-Wilk test, Spearman Correlation Analysis (Rs) and the Kruskal-Wallis test. The health sector with the highest percentages of confirmed dengue cases per year is Capim Dourado, except in 2017, and the Cerrado do Tocantins region had the lowest percentages; the years 2016 and 2019 had the highest incidences of confirmed cases in 10,000 inhabitants, with emphasis on the Capim Dourado and Médio Norte Araguaia regions, which exceeded 1900 cases per 10,000 inhabitants in 2019. There is no difference between the regions s when it comes to the number confirmed per 10,000 inhabitants. Regarding precipitation, it was observed that there is no heterogeneity between regions; the greater homogeneity of precipitation occurred between the regions Bico do Papagaio and Médio Norte Araguaia and the greater variability in the regions Capim Dourado and Cantão, which also had the highest total precipitation and the lowest, the Southeast region. In all regions the association of relative humidity (%) and total precipitation (mm) was significant at the 5% level. In the Cantão, Bananal Island and Southeast regions, the association between total precipitation (mm) and dengue cases was not significant, but in all regions the relative humidity (%) was significant with the number of dengue cases. Considering that the independent variables total precipitation (mm) and relative humidity (%) had a significant relationship at the 5% level, it is possible to choose one or the other variable for the study. The hypothesis that stated that the increasing number of new cases of arbovíruses in the health regions of the State of Tocantins is related to the months with higher rainfall and humidity was confirmed. New research should be developed in order to confirm how the temperature variable interferes in the results achieved.